A new species of Hemiphyllodactylus (Reptilia: Gekkonidae) from northern Laos - Nguyen, Truong Quang; Botov, Andreas; Le, Minh Duc; Nophaseud, Liphone; Zug, George; Bonkowski, Michael; Ziegler, Thomas (Zootaxa, 2014)
A new species of the genus Hemiphyllodactylus is described from Luang Prabang Province, northern Laos. Hemiphyllodactylus kiziriani sp. nov. is distinguished from the remaining congeners by morphology, coloration, and a significant genetic divergence of greater than 20% (ND2 gene). The new species from Laos is characterized by the following features: SVL of adult males 35.1–40.1 mm, of adult females 36.3–40.8 mm; dorsal scale rows 18–27; ventral scale rows 11–15; chin scales bordering mental and first infralabial distinctly enlarged; digital lamellae formulae 3-4-4-4 (forefoot) and 4-4/5-4/5-4 (hindfoot); femoral pores 0–4, total precloacal pores 10–13 in males, 8–10 pitted precloacal scales in females; cloacal spurs present in both sexes; dorsal trunk pattern dark brown with two rows of irregular transverse bands; dark lateral head stripe distinct; upper zone of flank with a dark brown stripe; caecum and gonadal ducts unpigmented.